4x-3 20-x 6x-7 11-x
F(x) = 2x^3 + 5x^2 -6x-7 g(x) = 2x-3 find (f 4x 3x x2 4x2 7x 6x 8x 10x 5x 6x brainly
F(x) = 2x^3 + 5x^2 -6x-7 g(x) = 2x-3 find (f - g) (x) - brainly.com
4x 6x solve example chapter ncert cbse inequalities linear class teachoo Answered: 3x + 3 :- x + 1 23. x +5 24. 4x +20 000… 4x 6x if fof show ex inverse teachoo
![Ex 1.3, 4 - If f(x) = 4x - 3 / 6x - 4, show that fof(x) = x](https://i2.wp.com/d1avenlh0i1xmr.cloudfront.net/61eb3af8-9596-44e4-9ede-2bb032111de8/slide8.jpg)
![Answered: 3x + 3 :- x + 1 23. x +5 24. 4x +20 000… | bartleby](https://i2.wp.com/prod-qna-question-images.s3.amazonaws.com/qna-images/question/5fa544c9-c440-4f94-850d-73173a8a80d4/1e170a85-1c8d-4f39-a576-a89966c2e284/bx1f4x.jpeg)
![Example 3 - Solve 4x + 3](https://i2.wp.com/d1avenlh0i1xmr.cloudfront.net/ba9a7c3c-6dae-4d1d-9335-eccab20aba52/slide5.jpg)
![F(x) = 2x^3 + 5x^2 -6x-7 g(x) = 2x-3 find (f - g) (x) - brainly.com](https://i2.wp.com/us-static.z-dn.net/files/de9/49beec843a6459886e104be82be1678e.png)